Telas fotosseletivas na produção de cultivares de manjericão em duas épocas de plantio - Nomura, Mirian (2020)
Basil, species Ocimum basilicum L. is an aromatic herb, whose essential oil is used as an industrial raw material. However, its biosynthesis varies greatly due to the interference of climatic, genetic and technological factors. The use of photoselective screens represents an alternative to maximize the productive potential of this species. The objective is to evaluate the effect of photoselective screens (Pearl, blue, red and black) on the chlorophyll fluorescence, biomass production and essential oil content and composition of four basil cultivars (Anise, Cinnamon, Italian Large Leaf and Maria Bonita), grown in spring/summer and fall/winter. The experiments of the two seasons were in a randomized block design, in a split plot scheme, testing five cultivation environments on the plots (three Chromatinet® photoselective screens in pearl, blue and red colors, all with 20% shading, and black screen with 30% shading, and a growing environment in full sun), and in the subplots four basil cultivars (Anise, Cinnamon, Italian Large Leaf and Maria Bonita). Contrast was performed, using the Scheffé test, to compare the culture under screens and in full sun. The data of the two growing seasons were submitted to joint analysis of variance and compared by the Tukey test at 5% probability. The cultivation of basil under photoselective screens increased the plant height, the blue screen for the cultivars Anise and Maria Bonita, pearl for Cinnamon and red for Italian Large Leaf provided greater fresh biomass of the aerial part in spring/summer cultivation. The essential oil yield was not affected by the screens, but by the season, being higher in the spring/summer cultivation. This season also provided better conditions for the functioning of the photosynthetic apparatus of the plants and resulted in higher levels of essential oil and its main constituents. The cultivar Maria Bonita showed the better performance of photosynthetic stooe and, consequently, higher content of essential oil. The screens did not promote variation in the chlorophyll fluorescence indices and the essential oil content, but they did change the concentration of the main constituents of the essential oils of all cultivars. The blue screen in the spring/summer cultivation increased the linalool content in the Cinnamon and Maria Bonita cultivars. The red screen increased the linalool content in the Italian Large Leaf cultivar and methyl chavicol in the Anise and Cinnamon cultivars in spring/summer cultivation. The pearl mesh in spring/summer cultivation increased the content of methyl (E)-cinnamate in the cultivar Cinnamon.